COVID-19 Health Risks and Labour Supply - Agarwal, Nalini; Bishop, James (My University, 2022)
There is evidence that concerns about becoming infected with COVID-19 at work have affected people's willingness to participate in the labour force in some countries. This article examines whether similar health concerns have contributed to a reduction in labour supply in Australia. It finds no evidence that these concerns had a discernible effect on labour supply during the COVID-19 outbreaks in 2020 and 2021. In early 2022, however, the substantial escalation in cases of the Omicron variant led a small number of people to avoid the workplace, at least temporarily.
Bulletin
Keywords: Health and wellbeing; Labour market